The Differential Effects of Subtitles on the Comprehension of Native English Connected Speech Varying in Types and Word Familiarity. (May 2020) - Wong, Simpson W. L.; Lin, Cherry C. Y.; Wong, Isabella S. Y.; Cheung, Anisa
Connected speech produced by native speakers poses a challenge to second language learners. Video subtitles have been found to assist the decoding of English connected speech for learners of English as a foreign language (EFL). However, the presence of subtitles may divert the listeners' attention to the visual cues while paying less attention to the speech signals. To test this proposal, we employed a bi-modal audio-visual listening test and examined whether EFL listeners were able to correctly identify the connected speech when misleading subtitles were present. We further tested whether connected speech with words of lower frequency further reduced the accuracy rate. Twenty-eight adolescent EFL learners, all with more than 10 years of experiences in learning English in schools, were tested with three major types of connected speech phonological processes, namely assimilation, elision, and juncture. The results of statistical analyses showed that matched and mismatched subtitles facilitated the comprehension of both familiar and unfamiliar connected speech. Error analyses revealed the degree of item-specific variations across the three types of connected speech processes as well as across the three subtitling conditions. This research provides insights on the immediate and long-term impact of subtitles on the decoding of English connected speech.